The Effectiveness of Using Blended Learning Methods to Improve Students' Cognitiveness in the Pandemic Era (Case Study : MTsN 3 Jombang) (SCHOOLAR: Social and Literature Study in Education, 2023)
The presence of the Covid-19 pandemic has had a very significant impact on several aspects of life, one of which is the education aspect. The government has started implementing social or physical distancing policies aimed at reducing the spread of the COVID-19 virus in Indonesia. So this requires that the implementation of education be carried out online remotely. By taking advantage of existing technological developments. In this pandemic situation, the blended learning method is an alternative way of implementing the teaching and learning process. The blended learning method is a method that uses two approaches at once. In the sense that this method uses an online system as well as face to face through video conferences.